Advertisement Remove all ads

The sum of n terms of three arithmetical progression are S1 , S2 and S3 . The first term of each is unity and the common differences are 1, 2 and 3 respectively. Prove that S1 + S3 = 2S2 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

The sum of n terms of three arithmetical progression are S1 , S2 and S3 . The first term of each is unity and the common differences are 1, 2 and 3 respectively. Prove that S1 + S3 = 2S2

Advertisement Remove all ads

Solution

We have,

S1 = Sum of n terms of an A.P. with first term 1 and common difference 1

`= \frac { n }{ 2 } [2 × 1 + (n – 1) 1] = \frac { n }{ 2 } [n + 1]`

S2 = Sum of n terms of an A.P. with first term 1 and common difference 2

`= \frac { n }{ 2 } [2 × 1 + (n – 1) × 2] = n^2`

S3 = Sum of n terms of an A.P. with first term 1 and common difference 3

`= \frac { n }{ 2 } [2 × 1 + (n – 1) × 3] = \frac { n }{ 2 } (3n – 1)`

Now,

`S_1 + S_3 = \frac { n }{ 2 } (n + 1) + \frac { n }{ 2 } (3n – 1)`

= 2n2 and S2 = n2

Hence S1 + S3 = 2S2

Concept: Sum of First n Terms of an AP
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×